Exploring the relationship between susceptibility to canine leishmaniosis and anti-Phlebotomus perniciosus saliva antibodies in Ibizan hounds and dogs of other breeds in Mallorca, Spain - Burnham, Alexis C; Ordeix, Laura; Alcover, M Magdalena; Martínez-Orellana, Pamela; Montserrat-Sangrà, Sara; Willen, Laura; Spitzova, Tatiana; Volf, Petr; Solano-Gallego, Laia (Parasites & vectors, 2020)
BACKGROUND: Canine leishmaniosis caused by Leishmania infantum is a neglected zoonosis transmitted by sand flies like Phlebotomus perniciosus. Clinical signs and disease susceptibility vary according to various factors, including host immune response and breed. In particular, Ibizan hounds appear more resistant. This immunocompetence could be attributed to a more frequent exposure to uninfected sand flies, eliciting a stronger anti-sand fly saliva antibody response. METHODS: This study aimed to investigate the prevalence of anti-P. perniciosus saliva antibodies in Ibizan hounds and dogs of other breeds in the Leishmania-endemic area of Mallorca, Spain, and to correlate these antibody levels with clinical, immunological and parasitological parameters. Anti-sand fly saliva IgG was examined in 47 Ibizan hounds and 45 dogs of other breeds using three methods: P. perniciosus whole salivary gland homogenate (SGH) ELISA; recombinant protein rSP03B ELISA; and rSP03B rapid tests (RT). Additionally, diagnostic performance was evaluated between methods. RESULTS: Results indicate significantly higher anti-SGH antibodies (P = 0.0061) and a trend for more positive SGH ELISA and RT results in Ibizan hounds compared to other breeds. General linear model analysis also found breed to be a significant factor in SGH ELISA units and a marginally significant factor in RT result. Although infection rates were similar between groups, Ibizan hounds included significantly more IFN-γ producers (P = 0.0122) and papular dermatitis cases (P < 0.0001). Older age and L. infantum seropositivity were also considered significant factors in sand fly saliva antibody levels according to at least one test. Fair agreement was found between all three tests, with the highest value between SGH and rSP03B RT. CONCLUSIONS: To our knowledge, this is the first study elaborating the relationship between anti-P. perniciosus saliva antibodies and extensive clinical data in dogs in an endemic area. Our results suggest that Ibizan hounds experience a higher frequency of exposure to sand flies and have a stronger cellular immune response to L. infantum infection than other breed dogs. Additional sampling is needed to confirm results, but anti-P. perniciosus saliva antibodies appear to negatively correlate with susceptibility to L. infantum infection and could possibly contribute to the resistance observed in Ibizan hounds.
Keywords: psi; Papular dermatitis; Breeding; Dogs; imunoglobulin G; Salivary Proteins and Peptides; hmyzí proteiny; Phlebotomus; Female; slinné proteiny a peptidy; Anti-sand fly saliva antibodies; chov; Spain; zoonózy; zvířata; endemické nemoci; Španělsko; náchylnost k nemoci; Disease Susceptibility; Saliva; Ibizan hounds; ženské pohlaví; leishmanióza; rSP03B; Male; Canine leishmaniosis; Phlebotomus perniciosus; nemoci psů; sliny; Zoonoses; Endemic Diseases; Dog Diseases; Leishmaniasis; Leishmania infantum; Animals; mužské pohlaví; Immunoglobulin G; Insect Proteins